HYBRID PARADIGM FROM EUROPEAN AND AMERICA CONCERNING PRIVACY AND PERSONAL DATA PROTECTION IN INDONESIA - Makarim, Edmon (Indonesia Law Review, 2013)
In the emerging era of information and technology, the importance of privacy and data protection is growing ever since. However, despite such common concern from the society, there is some confusion about the mechanisms of differentiation and scope of discussion about privacy with the protection of personal data and even impressed blended with issues of spamming issues. With comparison to Europe and the US legal perspectives, Therefore, this paper tries to discuss such problem in accordance to the perspective of laws to the communication itself.